2018
DOI: 10.24042/jipfalbiruni.v7i2.2898
|View full text |Cite
|
Sign up to set email alerts
|

5E-Learning Cycle Strategy: Increasing Conceptual Understanding and Learning Motivation

Abstract: 5E learning cycle strategy was students center oriented learning model. The learning process becomes more meaningful, which are prioritized authentic experience of students, made students become actively participating, able to critical thinking skills and creatively. The phases of the learning cycle 5E consist of engagement, exploration, explanation, elaboration, and evaluation. The purpose of the research was increased learning motivation and conceptual understanding improved by discovery learning due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 14 publications
3
30
0
4
Order By: Relevance
“…ICT technology-based learning also provides experience to improve the professional skills of prospective teachers who can be useful after they finish their studies in teacher education study programs for early childhood (Aoki, 2010;Aslan & Zhu, 2015;Relmasira & Thrupp, 2016). Seeing the importance of technology integration in learning (Putra, Nur Kholifah, Subali, & Rusilowati, 2018), especially for early childhood category students, researchers want to develop teaching materials titled child-friendly ICT as a guide for prospective teacher students to use technology in the learning process in the classroom.…”
Section: Figure 1 the Relationship Between Technology And Other Compementioning
confidence: 99%
See 1 more Smart Citation
“…ICT technology-based learning also provides experience to improve the professional skills of prospective teachers who can be useful after they finish their studies in teacher education study programs for early childhood (Aoki, 2010;Aslan & Zhu, 2015;Relmasira & Thrupp, 2016). Seeing the importance of technology integration in learning (Putra, Nur Kholifah, Subali, & Rusilowati, 2018), especially for early childhood category students, researchers want to develop teaching materials titled child-friendly ICT as a guide for prospective teacher students to use technology in the learning process in the classroom.…”
Section: Figure 1 the Relationship Between Technology And Other Compementioning
confidence: 99%
“…Another study concluded that by providing a safe web for children. Children's website is a great web that combines education (Putra et al, 2018) and entertainment (Misirli & Odabaşi, 2009). In addition, in order to be effective and directed at how students become optimally helped in the use of ICT in the learning process, the teacher needs to understand the importance of scaffolding and carry out the right scaffolding process for students (Rahman, Abdurrahman, Kadaryanto, & Rusminto, 2015;Nurulsari, Abdurrahman, & Suyatna, 2017).…”
Section: Calculation Of Chart Questionnaire Use Of "Ict Child Friendlmentioning
confidence: 99%
“…So that student center learning can be realized. With the teaching material, the learning process will become more organized, so that the specified competency targets can be achieved, and students are able to foster various abilities such as critical thinking and communication [2]- [4].…”
Section: Lembar Kerja Siswa (Lks) Berbasis Inkuiri Terbimbing Untuk Mmentioning
confidence: 99%
“…Various studies have proven that probing-prompting learning can improve cognitive abilities (Putra, Nur Kholifah, Subali, & Rusilowati, 2018). Some of them are that probing-prompting type cooperative learning can achieve learning completeness (Himatul Ulya, 2012), Metacognitive abilities of students are better after being given learning by probing techniques (Siregar, N. H., & Amin Fauzi, 2016), students are able to present mathematical statements verbally, written, drawings, and diagrams correctly after being given probing-prompting learning (Yayuk Kurniasari, 2013).…”
Section: Introductionmentioning
confidence: 99%